2010
DOI: 10.1016/j.athoracsur.2010.04.039
|View full text |Cite
|
Sign up to set email alerts
|

Duration of Acute Kidney Injury Impacts Long-Term Survival After Cardiac Surgery

Abstract: Background-Acute kidney injury (AKI) following cardiac surgery is associated with worse outcomes. However, it is not known how adverse long-term consequences vary according to the duration of AKI. We sought to determine the association between duration of AKI and survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
207
2
12

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 282 publications
(237 citation statements)
references
References 23 publications
16
207
2
12
Order By: Relevance
“…Regardless of disease severity, these studies demonstrate that complete and sustained reversal of an AKI episode within 48-72 h of its onset is associated with better outcomes than longer durations of AKI [10][11][12][13][14][15] . Based on the available data and expert opinion, the workgroup proposes using 48 h to define rapid reversal of AKI…”
Section: Persistent Aki Transient Versus Persistent Akimentioning
confidence: 76%
“…Regardless of disease severity, these studies demonstrate that complete and sustained reversal of an AKI episode within 48-72 h of its onset is associated with better outcomes than longer durations of AKI [10][11][12][13][14][15] . Based on the available data and expert opinion, the workgroup proposes using 48 h to define rapid reversal of AKI…”
Section: Persistent Aki Transient Versus Persistent Akimentioning
confidence: 76%
“…CPB-AKI has been consistently shown to increase both morbidity (4) and mortality (5). Likewise, AKI may also affect quality of life (6) and has an effect on mortality beyond the perioperative period (7).…”
Section: Introductionmentioning
confidence: 99%
“…3,4 These definitions have aided in ascertainment of the true incidence of AKI after cardiac surgery and shown that AKI, regardless of severity or stage, is associated with longer length of intensive care unit (ICU) and hospital stay, increased cost of hospitalization, and increased patient mortality. 5,6 In recent years, several studies have shown that novel biomarkers can detect acute tubular injury earlier than serum creatinine in the setting of AKI. [7][8][9][10][11] Despite attempts to select patients at high risk for severe AKI, the majority of patients in these prospective studies do not develop clinical AKI.…”
mentioning
confidence: 99%